Avaliação da quimioterapia metronômica em carcinomas mamários de cadelas por imunomarcações - Mendes, Analy Ramos [UNESP] (2014)
The canine mammary tumor (CMT) is the neoplasia that most commonly affects not spayed bitches. Therapy for CMT is a challenge since there are not described effective treatments for high-grade tumors. A therapeutic option that slows down tumor angiogenesis is metronomic chemotherapy (MC). Quantification of tumor angiogenesis has been proposed by measuring the vascular endothelial growth factor (VEGF) and microvessel density (MVD). Thus, in this study, the response of canine mammary carcinomas by the MC was evaluated by the measurement of MVD and tissue VEGF detection, apoptotic index (AI) and cell proliferation index (PI). Twenty-eight dogs with malignant CMT, equally distributed into a control group (CG) treated with mastectomy and a treated group (TG) treated with MC (cyclophosphamide 15mg/m2 and piroxicam 0.3 mg/kg) both orally and daily for 28 days followed by mastectomy. Mammary tumors were classified and graded histologically. MVD, tissue VEGF, AI and PI of all malignancies were obtained by immunostaining. The analysis showed statistical difference between groups in MVD and AI (p <0.05), showing quantitative reduction in tumor microvasculature and increase in tumor cells apoptosis. Based on this result, we can affirm that MC has antiangiogenic and proapoptotic effects in mammary carcinomas of bitches and can be used as a new therapeutic option